Metal-free amino acid glycine-derived nitrogen-doped carbon aerogel with superhigh surface area for highly efficient Zn-Air batteries. (15th October 2020) - Cai, Jia-Jun; Zhou, Qing-Yan; Gong, Xiao-Fei; Liu, Bing; Zhang, Yun-Long; Dai, Yun-Kun; Gu, Da-Ming; Zhao, Lei; Sui, Xu-Lei; Wang, Zhen-Bo
Abstract: Development of high-efficiency non-noble metal materials to substitute Pt-based catalysts for oxygen reduction reactions is crucial in the commercial viability of Zn-air batteries technology. Nitrogen doped carbons (NDCs) are highly appealing as promising candidates. This study reports a facile molten salt (MS) method to synthesize aerogel-like nitrogen doped carbon (NDC-MS). The eutectic mixture acting as combined solvent and porogen leads to the obtained porous materials with extremely large surface area (1548.6 m 2  g −1 ) and relatively high pore volume. The unique aerogel-like structure with hierarchical structure, increased catalytic active sits, extended surface area and large pore volume is beneficial for enhancing oxygen reduction reaction (ORR) performance. The resultant NDC-MS displays a superb ORR catalytic activity with high half-wave potential of 0.88 V, which is one of the most effective figures in previous literature of metal-free catalysts. The superb ORR performance can also be evaluated by Zn–air batteries with satisfactory power density and long-term operation stability. Therefore, such an efficient and green synthetic strategy can open up a new avenue for a wide range of commercial application of heteroatom doped carbon materials in advanced energy technologies. Graphical abstract: Image 1 Highlights: An aerogel-like nitrogen doped carbon catalyst is prepared by molten salt template method. Molten salt template works as structure-directing agent which guides the formation of unique 3D aerogel-like structure. NDC-MS exhibits a well-developed hierarchical structure, efficient doping and large surface area of 1548.6 m 2  g −1 . Unique features endow NDC-MS with superior ORR performance and satisfactory stability Zn-air battery.